Pengaruh Perkembangan Teknologi Inforomasi Terhadap Pola Hidup Masyarakat Suku Anak Dalam (SAD) Kec. Pelepat Ilir Kab. Bungo Prov. Jambi: Pengaruh Perkembangan Teknologi Inforomasi Terhadap Pola Hidup Masyarakat Suku Anak Dalam (SAD) Kec. Pelepat Ilir Kab. Bungo Prov. Jambi - Fathuroh, Siti (Sustainability (STPP) Theory, Practice and Policy, 2023)
The Anak Dalam Suku (SAD) community has wisdom values and social norms to guide the behavior and culture of its people. This article presents the results of identifying the wisdom values and social norms that guide the behavior of the SAD indigenous people who inhabit the Ds area. Source of hope (HTI) Kec. Pelepat Ilir district. Bungo, Jambi Province. Through observation, interviews, and focused dialogue with traditional leaders who play an important role in the SAD leadership structure, namely Tumenggung, Mangku, Depati, and Tengganai as well as community leaders, and guided by social construction theory which focuses on meaning, interpretation, and implications for organizational life and community networks, communication patterns are models of the communication process, so that with the existence of various communication models and parts of the communication process, patterns that are suitable and easy to use in communication can be found. In the beginning, communication between humans only exchanged information through language, by exchanging information directly through daily conversations. With the development of technology today, it makes the communication process easier without thinking about distance, space and time, it is easier to obtain information by getting it more quickly. This writing uses the literature study method. The aim of this research is to determine communication patterns between communities after technological advances. It is hoped that the benefits of this research can contribute to thinking and enrich insight for everyone. Keywords: Technology; Communication; information; Jambi Community; Inner Tribe (SAD).